Effects of imipramine on cancer patients over-expressing Fascin1; description of the HITCLIF clinical trial - Asensi-Cantó, Antonio; Rodríguez-Braun, Edith; Beltrán-Videla, Asunción; Hurtado, Ana María; Conesa-Zamora, Pablo (Frontiers in Oncology, 2023)
Background: Tumor invasion and metastasis are responsible for the majority of cancer-related deaths. To spread and metastasize, tumor cells must restructure their cytoskeleton and emit protrusions. A key molecule in this process is Fascin1, the main protein involved in the formation of actin cytoskeleton bundles and a consistent marker of bad prognosis in several types of cancer. Its expression is virtually absent in normal epithelia but highly expressed in cancer cells. In silico, in vitro and in vivo studies by our group have demonstrated that the FDA-and EMA-approved antidepressant imipramine has Fascin1-dependant anti-invasive and antimetastatic effects in colorectal cancer cells, thus, making it a promising candidate for the treatment of Fascin1 expressing cancers. As a result, a clinical trial is being conducted to assess the efficacy of imipramine being the first experimental clinical study selecting patients based on Fascin1 expression. The HITCLIF trial is a multicenter, double-blind, placebo-controlled, randomized and non-commercial phase II clinical trial conducted in parallel groups to evaluate the effectiveness of imipramine, as anti-invasive agent, in the treatment of localized colon, rectal and triple negative breast cancer patients with Fascin1 overexpression. Eligible patients will be randomly assigned, in a 1:1 ratio, to receive imipramine or placebo. Patients are being stratified into 2 groups according to whether administration of imipramine is concomitant with neoadjuvant chemotherapy regimen. Group A will receive imipramine alone without neoadjuvant chemotherapy, while Group B will receive imipramine treatment along with the standard neoadjuvant chemotherapy regimen. The primary endpoint of the trial is the grade of alteration in the prognostic histopathological features at invasive margins (tumor budding, cytoplasmic pseudofragments, tumor growth pattern, and peritumoral lymphocytic infiltration). Therefore, the administration of imipramine are being carried out during the period between the diagnosis biopsy and surgical resection to explore the drug effects on tumor invasive front. Preliminary results with six patients recruited so far demonstrate good safety profile.